2015
DOI: 10.1007/s12666-015-0694-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Friction Stir Welds in AA2219-AA5083 Aluminium Alloys: Effect of Process Parameters on Material Inter-Mixing, Defect Formation, and Mechanical Properties

Abstract: Dissimilar friction stir welds of aluminium alloys AA 5083 and AA2219 were investigated in a view to get defect free welds by varying process parameters. An attempt has been made to develop a mathematical model to predict sound welds. Design of experiments with three parameters and five levels were used to optimize the effectiveness of process parameters. Analysis of variance and response surface methodology were used to determine the significance and optimal level for each parameter to minimize % area of volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Kalemba-Rec et al [16] showed a proportional relationship between material mixing and tool rotation speed for a dissimilar AA7075-AA5083 joint. However, very large rotation speeds lead to numerous imperfections such as poor surface (flash), voids, porosity, tunneling or formation of wormholes because of the excessive heat input [75][76][77], as shown In the case of the lap joint, the BM placement affects the material flow and leads to the generatio the ubiquitous hook defect. Now the material movement is in an upward direction that is, from bottom sheet to the top sheet, creating hook defects of various sizes.…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kalemba-Rec et al [16] showed a proportional relationship between material mixing and tool rotation speed for a dissimilar AA7075-AA5083 joint. However, very large rotation speeds lead to numerous imperfections such as poor surface (flash), voids, porosity, tunneling or formation of wormholes because of the excessive heat input [75][76][77], as shown In the case of the lap joint, the BM placement affects the material flow and leads to the generatio the ubiquitous hook defect. Now the material movement is in an upward direction that is, from bottom sheet to the top sheet, creating hook defects of various sizes.…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
“…Kalemba-Rec et al [16] showed a proportional relationship between material mixing and tool rotation speed for a dissimilar AA7075-AA5083 joint. However, very large rotation speeds lead to numerous imperfections such as poor surface (flash), voids, porosity, tunneling or formation of wormholes because of the excessive heat input [75][76][77], as shown in Figure 7. Low welding speeds increase heat input and are associated with defects like tunneling [55,58,75,78,79].…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Including three repeat runs for the central points (for which all factors are kept at their intermediate levels; coded value: 0) makes a total of 15 runs [31]. Applications of response surface methodology for investigating effects of friction stir welding process parameters on tensile properties or other responses have been reported in the literature [32][33][34][35]. Ghetiya and Patel [32] developed a mathematical model for prediction of tensile strength of AA2014-T4 immersed friction stir welds using Box-Behnken design.…”
Section: Introductionmentioning
confidence: 99%
“…A low rotational speed or a higher traverse speed cause tunneling defect and kissing bond due to insufficient material mixing as the heat input is too low and the material is not soft enough [27]. On the other hand, a combination of high speeds and high traverse speeds causes cavities due to abnormal stirring [28]. In the range of optimized welding parameters, increasing the traverse speed in the presence of a constant rotational speed improves joint mechanical properties [29], while increasing the rotational speed results in higher heat input and lower mechanical properties [30].…”
Section: Introductionmentioning
confidence: 99%